4 - The Impact of Agricultural Extension Service on the Uptake of Various Agricultural Technologies in Ethiopia - Hiwot, Mesfin; Tirivayi , Nyasha; Nillesen , Eleonora; Tessema , Yohannis M. (Africa Development, 2022)
Many governments provide a free agricultural extension service that aims to link farmers to scientific knowledge and yield-enhancing technologies. However, the impact of this service in achieving its aim has been unclear. This study focuses on Ethiopia to explore the impact of the agricultural extension service on farmers’ utilisation of various agricultural technologies. Using a large and representative data set, the study applies an instrumental variable method, along with other robustness checks, and finds that the impact of the extension service is heterogeneous to the type of farm technologies. The study finds that the agricultural extension service has a positive impact on chemical fertiliser and crop rotation use, but a negative impact on organic fertiliser use, and no impact on pesticide, herbicide and fungicide use. Based on these results, policy-makers interested in promoting the utilisation of organic fertiliser need to retrain the extension agents and redirect their efforts towards recommending organic fertilisers as much as they do chemical fertilisers and crop rotation.